Portaria PRCE nº 626, de 30 de novembro de 2015 - Samuel Miranda Arruda (DMPF-e, Brasília, DF, 30 nov. 2015. Caderno administrativo, p. 31., 2015)
Altera Portaria/GAB/Chefia nº 612, de 23 de novembro de 2015.